2021
DOI: 10.5937/jaes0-28855
|View full text |Cite
|
Sign up to set email alerts
|

Development of equipment management system with monitoring of working characteristics of technological processes

Abstract: The work provides multi-purpose optimization of the baklava production process based on technology of agent systems, the intelligent environment of process control systems. The general architecture of the control system intelligent environment with agent technologies for recognizing abnormal situations was developed and adaptive baklava production regulators were synthesized. It allows you to get the specified dynamic characteristics of the control object based on the developed adaptive systems for adjusting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…The system provides the ability to quickly reorient production in response to changing market conditions [24].…”
Section: Resultsmentioning
confidence: 99%
“…The system provides the ability to quickly reorient production in response to changing market conditions [24].…”
Section: Resultsmentioning
confidence: 99%
“…The scientific basis for the study of the processes observed in modern Western agricultural agricultural cooperatives was provided by the most valuable materials of theoretical and empirical research on the characteristics (including problems) of the functioning of European cooperatives, in particular one of such outstanding representatives as the dairy cooperative "Arla Foods" , the development of which is accompanied by the tendencies inherent in many successful cooperatives: consolidation (through mergers and acquisitions); diversification of production; acquiring a transnational character of activity (Azuayi, 2016;Gaither, et al, 2008;Andersen, 2007;Belousova et al, 2021;Vigliarolo, 2020;Cheremisina et al, 2018). In addition, the work used statistical (and other) information about the functioning of "Arla Foods" obtained from the official website of the company, including from its two latest reports: 1) 2019 report, the emphasis in which is mainly on economic and financial results of the cooperative's activities (Leading Through Sustainable Business Performance); 2) the 2020 report, reciting the data given in it around the problem of the company's sustainable development, including during the COVID-19 pandemic and overcoming its consequences (Accelerating Sustainability Actions in Challenging Times).…”
Section: Methodsmentioning
confidence: 99%
“…It was also identified that ethnic entrepreneurs were the driving force behind social, economic and physical transformations in three districts of the city of Toronto. The empirical data obtained is believed to enable the municipalities of Toronto to design a more flexible and effective support program for ethnic entrepreneurs, which is expected to have a beneficial effect on business climate [12,13].…”
Section: Methodsmentioning
confidence: 99%